1977
DOI: 10.1007/bf02139083
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in sex-role conceptions and family orientation of high school students

Abstract: Studies of college freshmen find that men are more sexist in their attitudes than women. Does this hold also for high school students? This paper reports the relationship of (1) sex-role attitudes to selected school and family characteristics and (2) attitudes toward family life to sex-role conceptions for women and men. The study is based on 529 students in grades 9 to 12 attending four high schools. The findings show that males are more sexist than females and Blacks more so than Whites. Women who are bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Yet within this moderation, the majority of the attitudinal items elicited a significantly more nontraditional response from females, a finding supported by previous research (Parelius, 1975;Scanzoni, 1976;Bayer, 1975;Angrist et al, 1977).…”
Section: Resultssupporting
confidence: 83%
“…Yet within this moderation, the majority of the attitudinal items elicited a significantly more nontraditional response from females, a finding supported by previous research (Parelius, 1975;Scanzoni, 1976;Bayer, 1975;Angrist et al, 1977).…”
Section: Resultssupporting
confidence: 83%
“…The consistent tendency for males to be somewhat more conservative, on the average, confirms other reports of more traditional sex-role attitudes in males than in females (Angrist et al, 1977;Osmand & Martin, 1975). It still seems to us that the level of sex differences observed in our data are not pronounced enough to predict widespread and fundamental disagreement between the sexes about the proper roles for husbands and wives.…”
Section: Sex Differences In Preference Patternssupporting
confidence: 85%
“…The evidence on all these questions is incomplete and inconsistent. Some investigators have observed trends towards egalitarian attitudes among college students (Bayer, 1975;Parelius, 1975), but others have reported considerable conservatism among high school students, and in some instances also among college students (Angrist, Mickelsen, & Penna, 1977;Christensen, 1961;Dunn, 1960;Nelson & Goldman, 1969;Osmond & Martin, 1975;Payne, 1956). Many of the latter studies suffer from methodological limitations such as old and possibly obsolete data, use of local samples of students, or question formats not detailed enough to enable a careful analysis of the range of possible attitudes.…”
mentioning
confidence: 99%
“…The middle-class white adolescents in the Emmerich and Shepard study (1982) had lower gendertyped preferences; the black sample working-class girls were more stereo-typed in early adolescents than were middle-class girls (Cummings and Taebel, 1980). Canter and Ageton (1984), Angrist, Mickelsen and Penna (1977) and Romer and Cherry (1980) also found some support for less traditionality in middle-class subjects.…”
Section: The Effects Of Distal Family Variables On Gender Schematamentioning
confidence: 89%